Experimental Investigation of the Micro-Milling of Additively Manufactured Titanium Alloys: Selective Laser Melting and Wrought Ti6Al4V - Muhammad Rehan; Tao He; Ahmed K. Khalil; Danish Tahir; Wai Sze Yip; Sandy Suet To (Chinese Journal of Mechanical Engineering)
Abstract In recent years, additive manufacturing (AM) has gained popularity in the aerospace, automobile, and medical industries due to its ability to produce complex profiles with minimal tolerances. Micro-milling is recommended for machining AM-based parts to improve surface quality and form accuracy. Therefore, the machinability of a titanium alloy (Ti6Al4V) manufactured using selective laser melting (SLM) is explored and compared to that of wrought Ti6Al4V in micro-milling. The experimental results reveal the surface topology, chip morphology, burr formation, and tool wear characteristics of both samples. The micro-milling of AM-based Ti6Al4V generates a surface roughness of 19.2 nm, which is 13.9% lower than that of wrought workpieces, and this component exhibits less tool wear. SLM-based Ti6Al4V produces continuous chips, while wrought Ti6Al4V yields relatively short chips. Additionally, SLM-fabricated Ti6Al4V exhibits smaller burrs after micro-milling than wrought Ti6Al4V. Despite the higher hardness of SLM-based Ti6Al4V, it demonstrates better machinability than wrought Ti6Al4V, resulting in better surface quality with lower tool wear levels and shorter burr heights. This study provides valuable insights into future research on postprocessing AM-based titanium parts, especially using micro-milling.